2019
DOI: 10.3389/fmed.2018.00364
|View full text |Cite
|
Sign up to set email alerts
|

IL-17 in Rheumatoid Arthritis and Precision Medicine: From Synovitis Expression to Circulating Bioactive Levels

Abstract: Interleukin (IL)-17A has a direct contribution in early induction and late chronic stages of various inflammatory diseases. In vitro and in vivo experiments have first characterized its local effects on different cell types and then its systemic effects. For instance, IL-17 axis is now identified as a key driver of psoriasis through its effects on keratinocytes. Similar observations apply for rheumatoid arthritis (RA) where IL-17A triggers changes in the synovium that lead to synovitis and maintain local infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
91
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(106 citation statements)
references
References 105 publications
(150 reference statements)
4
91
0
2
Order By: Relevance
“…Recent studies have suggested that knee OA might be considered a chronic inflammatory disorder, elevated levels of IL-1, IL-6, IL-17,TNF-α, and other acute-phase proteins that are found in patients with cartilage degradation [25]. A kind of conventional viewpoint is that inflammatory mechanism plays a crucial role in the pathogenesis and evolution of cartilage degeneration and expression of inflammatory reaction [26][27][28]. IL-17 is one of the most important regulators of innate and adaptive immune responses, and it is expressed in synovial tissues, and could contribute to cartilage degeneration and synovial infiltration in joint by inducing the release of chemokines by chondrocytes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that knee OA might be considered a chronic inflammatory disorder, elevated levels of IL-1, IL-6, IL-17,TNF-α, and other acute-phase proteins that are found in patients with cartilage degradation [25]. A kind of conventional viewpoint is that inflammatory mechanism plays a crucial role in the pathogenesis and evolution of cartilage degeneration and expression of inflammatory reaction [26][27][28]. IL-17 is one of the most important regulators of innate and adaptive immune responses, and it is expressed in synovial tissues, and could contribute to cartilage degeneration and synovial infiltration in joint by inducing the release of chemokines by chondrocytes [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Extracts #4, #6, #8, #13 and #14 down-regulated, while extract #12 upregulated IL-23A, a member of the IL-12 family of cytokines with pro-in ammatory properties 19 . Extracts #8 and #13 downregulated IL-17C, a pro-in ammatory cytokine and a member of IL-17 family, that, together with IL-23 mediates in ammation in psoriasis, psoriatic arthritis, and ankylosing spondylitis 20 . Increased expression of IL-23/IL-17 pathway was previously correlated with pulmonary in ammation in polymicrobial sepsis 21 .…”
Section: Resultsmentioning
confidence: 99%
“…IL-17A produced by Th17 cells promotes both the production of the pro-inflammatory cytokines IL-6, IL-8, and GM-CSF from epithelial, endothelial, and fibroblastic cells [68] and neutrophil recruitment [69], which leads to local inflammation and promotes disease progression. By these actions, IL-17A contributes to bone erosion, cartilage destruction, and neoangiogenesis in RA patients [70]. IL-17A triggers differentiation of osteoclast progenitors into mature osteoclasts and promotes RANK-L production by osteoblasts and synoviocytes, resulting in both reduced bone formation and enhanced bone erosion [71][72][73].…”
Section: Contribution Of Cytokines To Inflammation In Ramentioning
confidence: 99%